Pelatihan Manajemen Sumber Daya Manusia Hijau Dalam Mempertahankan Persaingan - Aisah, Siti Nur (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2024)
The training aims to provide an overview of Green Human Resource Management (Green HRM), because it is related to environmental aspects with preserving nature in its management. Training is important in efforts to preserve the environment with Green HRM being able to have a positive influence on nature. The problem with MSMEs is that there is still minimal knowledge and practice regarding Green HRM in preserving nature in its management. The aim of community service is to provide simple Green HRM training which can increase awareness of preserving nature. The benefit of this activity is to provide knowledge about preserving nature in its management. The which includes: preparation, planning and evaluation stages. It is hoped that this community service activity can help MSMEs increase understanding and awareness about environmentally friendly HRM so that they can survive in competition.